A framework for regional estimation of intensity–duration–frequency (IDF) curves. Issue 14 (27th May 2014) - Burn, Donald H.; Carey, Sean; Quinton, Bill
Abstract A regional, or pooled, approach to frequency analysis is explored in the context of the estimation of rainfall quantiles required for the formation of intensity–duration–frequency (IDF) curves. Resampling experiments are used, in conjunction with two rainfall data sets with long record lengths, to explore the merits of a pooled approach to the estimation of extreme rainfall quantiles. The width of the 95% confidence interval for quantile estimates is used as the primary basis to evaluate the relative merits of pooled and single site estimates of rainfall quantiles. Recommendations are formulated for applying the regional approach to frequency analysis, and these recommendations are used in the application of the regional approach to 40 sites with IDF data in southern Ontario, Canada. The results demonstrate that the regional approach is preferred to single site analysis for estimating extreme rainfall quantiles for conditions and data availability commonly encountered in practice. Copyright © 2014 John Wiley & Sons, Ltd.